In search of our mothers' gardens womanist prose - Walker, Alice (Harcourt Brace, 1983)
In this, her first collection of nonfiction, Alice Walker speaks out as a black woman, writer, mother, and feminist. Among the thirty-six pieces are essays about other writers, accounts of the civil rights movement of the 1960s and the anti-nuclear movement of the 1980s, and a vivid memoir of a scarring childhood injury and her daughter’s healing words.
Keywords: 1900-1999; amériques; approches et analyses; arts; cours; cycles supérieurs; discipline; droits civiques; fem1000; fem3300; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; womanist; états-unis; études littéraires